Sensitive Detection of 8-Nitroguanine in DNA by Chemical Derivatization Coupled with Online Solid-Phase Extraction LC-MS/MS - Chiung-Wen Hu (Molecules, 2018)
8-Nitroguanine (8-nitroG) is a major mutagenic nucleobase lesion generated by peroxynitrite during inflammation and has been used as a potential biomarker to evaluate inflammation-related carcinogenesis. Here, we present an online solid-phase extraction (SPE) LC-MS/MS method with 6-methoxy-2-naphthyl glyoxal hydrate (MTNG) derivatization for a sensitive and precise measurement of 8-nitroG in DNA. Derivatization optimization revealed that an excess of MTNG is required to achieve complete derivatization in DNA hydrolysates (MTNG: 8-nitroG molar ratio of 3740:1). The use of online SPE effectively avoided ion-source contamination from derivatization reagent by washing away all unreacted MTNG before column chromatography and the ionization process in mass spectrometry. With the use of isotope-labeled internal standard, the detection limit was as low as 0.015 nM. Inter- and intraday imprecision was <5.0%. This method was compared to a previous direct LC-MS/MS method without derivatization. The comparison showed an excellent fit and consistency, suggesting that the present method has satisfactory effectiveness and reliability for 8-nitroG analysis. This method was further applied to determine the 8-nitroG in human urine. 8-NitroG was not detectable using LC-MS/MS with derivatization, whereas a significant false-positive signal was detected without derivatization. It highlights the use of MTNG derivatization in 8-nitroG analysis for increasing the method specificity.